IMPLEMENTASI INOVASI LAYANAN GAWAT DARURAT ‘BRIGADE KUPANG SEHAT’ DI KOTA KUPANG - Muda, Blida; Molan, Kristianus Simon Hale; Ratumakin, Paulus Adrianus K.L. (JAP UNWIRA, 2025)
AbstractBrigade Kupang Sehat (BKS) is a functional unit at the Kupang City Health Office that provides emergency services using a ball pick-up model and has been implemented since 2014. This study aims to identify and analyze the content and context of the BKS program. The method used in this research is descriptive qualitative. The research was carried out for one month (May-June 2022). Data collection was carried out by interviews, observation and document study. There were ten informants in the study who were selected using a purposive sampling technique. The results of the study show that the implementation of the BKS program opens access for people who need health services quickly and easily. The success of the program is supported by the commitment of the Government and the Regional People's Representative Council (DPRD) of the City of Kupang as well as adequate human resources, capital and facilities. With advances in technology and information, it is hoped that the Kupang city government will need to develop a special location marker application to make it easier for the BKS team to find the patient's location point.
Keywords: Keyword; Implementation; Content; Context; Brigade Kupang Sehat